Awareness about antiretroviral treatment, intentions to use condoms, and decisions to have an HIV test among rural northern lowland Thai and ethnic minority young adults - Srithanaviboonchai K. (2017)
Young adults aged 18 to 32 years were randomly selected from a household probability sample participating in Project Accept in the remote areas of Chiang Mai province in northern Thailand in 2005. Among 2989 respondents, 44.4% had never heard of antiretroviral treatment (ART). Lack of awareness of ART was independently associated with having had no formal education compared with some formal education and being an ethnic minority compared with being Thai. In all, 57% of the respondents who had ever heard of ART stated that if ART were easily available in their communities it would affect their intentions to be tested for HIV, whereas only 36% stated that this would affect their intentions to use condoms. Younger participants were less likely to intend to get an HIV test as compared with older individuals, and ethnic minorities were less likely to report that they would get an HIV test compared with Thai lowlanders. Single individuals and people who lived separately from their spouses were more likely to have the intention to use condoms if ART were available. © 2010 APJPH.